The man who was Poe - Avi, 1937- (New York : Avon/Flare Book, 1991)
In Providence, R.I., in 1848, Edgar Allan Poe reluctantly investigates the problems of eleven-year-old Edmund, whose family has mysteriously disappeared and whose story suggests a new Poe tale with a ghastly final twist.
"First Avon Flare printing"--T.p. verso.
5.9
5-8
5-8.
Wilson's Junior High School
Booklist
Keywords: Poe, Edgar Allan, -- 1809-1849 -- Fiction; Providence (R.I.) -- Fiction; Mystery and detective stories; Historical fiction; Poe, Edgar Allan, -- 1809-1849 -- Fiction; Providence (R.I.) -- Fiction; Mystery fiction; Historical fiction